PENGARUH MOTIVASI KERJA TERHADAP KINERJA DOSEN STIE TOTALWIN SEMARANG - Hakim, Lukmanul (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2011)
Organization as a system of behavior included input, process and output. A collection of people, facilities and infrastructure could be used as input for further processing. Form and the process can be the interaction of people involved in the organization. The form of output was a result of cooperation in implementing something to achieved the same goal. The general purpose of operation can not function when not translated into specific objectives. Its not easy to measure achievement objectives for organizations that do not produce tangible outputs such as in the College of Economics Totalwin Semarang engaged in the business of education services. In such organizations, faculty and staff input is a factor that perform a process inorder to create good output. One of the problems still faced by the existing College of Economics Totalwin Semarang until now was